Seroprevalence of TORCH Infections in Children - Biswas, Sanjoy Kanti; Badruddoza, Md; Sultana, Nahid (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background : The acronym “TORCH” was introduced to highlight a group of pathogens that cause a congenital and perinatal infections: Toxoplasma gondi, rubella virus, Cytomegalovirus (CMV) and Herpes Simplex Virus (HSV). These pathogens are often associated with congenital anomalies. Congenital malformations have a direct impact on the family. This study was undertaken to detect the serological evidence of TORCH infections in children, by establishing the presence of specific IgM antibodies. Methods: During the period 1st June 2016 to 30th May 2017, 58 suspected TORCH infection cases were included from Paediatrics Department of CMOSH for TORCH antibody detection. The children were in the age of 0 day to 1 year with an average age of 3.3±2.59 months. The serum samples were tested forIgM and IgG antibodies against TORCH agents by using enzyme linked immunoassay method (ELISA). Results: Among the 58 children, seropositivity was found in 55 (94.82%) cases. Of the 55 seropositive cases serological evidence for combination of IgM and IgG with any one of the TORCH agents was detected in 25 (43.10%) and IgG alone was detected in 30 (51.72%) children. IgM/IgG antibody positivity to Toxoplasma, Rubella, CMV and HSV was 21(36.21%), 50(86.21%), 52(89.66%) and 8(13.79%) respectively. IgM anti-CMV were observed in highest number of cases 19(32.76%), followed by IgM anti-rubella 7(12.07%). IgM against HSV and Toxoplasma were found in equal number of cases, 3(5.17%) each. Conclusions: Awareness amongst clinicians and mothers about TORCH infections and their consequences should be developed. Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 13-16